Pengaruh E-service quality, Product quality, dan Consumer trust Terhadap Buying decision Paket Premium Pada Aplikasi Spotify - Farhana, Nur Zaidah; Sudaryanti, Dwiyani; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to identify the effect of E-service quality, Product quality and Consumer trust on Buying decisions for premium packages on the Spotify application. This type of research uses a quantitative approach. The population in this study were users of the Spotify premium Spotify application in Malang City. The sampling technique used purposive sampling with a sample of 75 respondents. The data was obtained from a questionnaire using a Likert scale. This research data analysis uses multiple linear regression analysis. This research contributes to understanding the factors that influence purchasing decisions for premium packages in the Spotify application. The results of this study are E-service quality and Product quality have an effect on Buying decisions partially, while Consumer trust has no partial effect. Simultaneously E-service quality, Product quality and Consumer trust have an effect on Buying decisions for premium packages in the Spotify application. Keywords: Buying Decision, E-Service Quality, Product Quality, And Consumer Trust